Adaptive molecular convergence is pervasive across deep time and largely decoupled from phenotypic convergence - Cory A. Berger; Marina I. Stoilova; Rebecca M. Varney; Sam C. Abrams; Maria Pia Miglietta; Paulyn Cartwright; Todd H. Oakley (Proceedings of the National Academy of Sciences, 2026)
Reuse of homologous genes during the evolution of similar traits or ecological transitions is often taken as evidence that evolution is repeatable at the molecular level. To study gene reuse, biologists frequently select specific convergent phenotypes and search for signatures of natural selection in genomes associated with those phenotypes. However, the causes and frequency of genome-scale molecular convergence remain unresolved, especially over deep timescales. We use phylotranscriptomics and analyses of sequence evolution to show that adaptive molecular convergence—defined as excess convergence of nonsynonymous substitutions between homologs, consistent with positive selection—is widespread across Medusozoa. Molecular convergence declines slightly over time but persists among lineages separated by over 600 My, consistently exceeding null expectations based on random overlap. Moreover, lineages sharing repeatedly evolved phenotypes (eyes, medusa loss, and upright colonies) do not exhibit elevated molecular convergence relative to other comparisons. Instead, convergence occurs idiosyncratically among species pairs and is broadly concentrated in genes associated with environment-facing functions, including metabolism, immunity, and xenobiotic processing. Our results suggest that selection often drives similar protein substitutions in disparate lineages, but that the selective causes of molecular convergence reflect multifaceted, lineage-specific interactions between organisms and their environments.